Costs of Technical Violation of Accounting-Based Debt Covenants - Beneish, Messod D.; Eric Press (The Accounting Review, 1993)
[Costs associated with the violation of accounting-based covenants in debt agreements are presumed to be material by both accounting regulators and researchers. The Financial Accounting Standards Board, for example, delayed the implementation of its pronouncement on pension reporting, SFAS No. 87, for two years to allow firms sufficient time to "renegotiate or to obtain waivers of provisions of some legal contracts" (FASB 1985, par. 260). Numerous studies in accounting research hypothesize that it is costly for firms to violate accounting covenants in debt agreements, and this supposition figures in research on such issues as the economic impact of mandated and voluntary accounting changes (see, e.g., Holthausen 1981; Leftwich 1981; Lys 1984) and the determinants of accounting choice (see, e.g., Trombley 1989; Zmijewski and Hagerman 1981). Although research in financial economics has studied some of the costs shareholders bear when there are debt service defaults or bankruptcy filings, the costs associated with technical violation-the violation of covenants other than debt service-have not been documented. This study investigates the costs of technical violation for a sample of 91 firms that violated accounting-based covenants in debt agreements between 1983 and 1987. The sample includes firms for which the technical violation was sufficiently material to merit disclosure. We provide direct evidence of refinancing and restructuring costs by examining changes in terms of debt agreements, and changes in investing and financing decisions. Refinancing costs arise because lenders raise interest rates on loans and notes following violation. We estimate that increased interest costs resulting from violation range between 0.84 and 1.63 percent of the market value of sample firms' equity. Restructuring costs stem from lenders' demands for partial or full repayment. Nearly half the sample firms either refinanced their debt or divested assets within one year of violation, stating that the proceeds were to reduce the outstanding balances of violated debt agreements. We estimate that the costs of restructuring debt represent an average of 0.37 percent of sample firms' market value of equity. We also present some evidence that there are costs associated with modifying operations, although we cannot estimate their magnitude; lenders' repayment demands impose restructuring costs by forcing firms to eliminate profitable investment projects. In addition to these costs, increased lender control is an important effect of technical violation. We observe that lenders add numerous new covenants. Interestingly, few of these are accounting-based, which suggests that only slight adjustments to accounting-based monitoring are required. The majority of new covenants consists of restrictions on investing and financing to prevent further dissipation of assets. We consider whether the costs of technical violation vary according to lender response. We find that the costs are lower for firms that can obtain a waiver than for those that cannot. More important, the evidence suggests that lenders often extract fees and concessions from violators in exchange for granting waivers. This is one of the first studies to substantiate that technical violation of accounting-based covenants is costly. Depending on the assumptions made, the average costs we estimate range between 1.2 and 2 percent of market value of equity; alternatively, the losses represent between 4.4 and 7.3 percent of the outstanding balances of the violated debt agreements. Evidence on the costs of technical violation is relevant to researchers who attribute economic consequences to changes in debt covenant slack and the likelihood of violating accounting-based covenants. Furthermore, by showing that leverage proxies for the magnitude of some of the costs imposed by technical violation, we justify the use of this surrogate in accounting research.]